CO_2 dissolution in a background hydrological flow. (26th January 2016) - Unwin, H. Juliette T.; Wells, Garth N.; Woods, Andrew W.
Abstract : During CO_2 sequestration into a deep saline aquifer of finite vertical extent, CO_2 will tend to accumulate in structural highs such as offered by an anticline. Over times of tens to thousands of years, some of the CO_2 will dissolve into the underlying groundwater to produce a region of relatively dense, saturated water directly below the plume of CO_2 . Continued dissolution then requires the supply of unsaturated aquifer water. In an aquifer of finite vertical extent, this may be provided by a background hydrological flow, or a laterally-spreading buoyancy-driven flow caused by the greater density of the CO_2 saturated water relative to the original aquifer water. We investigate long time steady-state dissolution in the presence of a background hydrological flow. In steady state, the distribution of CO_2 in the groundwater upstream of the aquifer involves a balance between three competing effects: (i) the buoyancy-driven flow of CO_2 saturated water; (ii) the diffusion of CO_2 from saturated to under-saturated water; and (iii) the advection associated with the oncoming background flow. This leads to three limiting regimes. In the limit of very slow diffusion, a nearly static intrusion of dense fluid may extend a finite distance upstream, balanced by the pressure gradient associated with the oncoming background flow. In the limit of fast diffusion relative to the flow, a gradient zone may become established in which the along-aquifer diffusive flux balances the advection associated with the background flow. However, if the buoyancy-driven flow speed exceeds the background hydrological flow speed, then a third, intermediate regime may become established. In this regime, a convective recirculation develops upstream of the anticline involving the vertical diffusion of CO_2 from an upstream propagating flow of dense CO_2 saturated water into the downstream propagating flow of CO_2 unsaturated water. For each limiting case, we find analytical solutions for the distribution of CO_2 upstream of the anticline, and test our analysis with full numerical simulations. A key result is that, although there may be very different controls on the distribution and extent of CO_2 bearing water upstream of the anticline, in each case the dissolution rate is given by the product of the background volume flux and the difference in concentration between the CO_2 saturated water and the original aquifer water upstream.